Non Linear optical properties of silver nanoparticles doped polyvinyl alcohol - Alnayli, R. Sh.; Alkazaali, Hanan (Al-Qadisiyah Journal of Pure Science, 2018)
In the present work, synthesis silver nanoparticle by laser ablation by using (Q -switched Nd:YAG) pulse duration(E=80mJ, Î»=532nm) of silver metal target in ethanol,Z-scan technique was used to study the nonlinear optical properties, represented by the nonlinear refractive index and nonlinear absorption coefficients of Ag NPs/PVA.In this technique, used CW diode laser (Î»= 650nm,p=50mw).The results show that the nonlinear refractive indexnegative (self-defocusing) and nonlinear absorption coefficients two photonabsorption (TPA).